100 Innovations That Transformed Tourism. (January 2015) - Hjalager, Anne-Mette
This article provides a systematized and analytically concise collection of 100 innovations that were not specifically invented for tourism but nevertheless affected tourism to a significant extent. The article is a contribution to tourism history, and it introduces a new facet of tourism innovation research. Scientific and technological progress facilitates the development of tourism, but often with some delay. The trickling down depends on institutional changes and absorptive capacity in the tourism sector. The impacts contributed mainly to the social and physical efficacy of tourists, including reduction of risks and improved mobility and accessibility. Innovations also laid the ground for entirely new touristic experiences. Numerous innovations were implemented to increase the productivity and performance of tourism enterprises. The article provides examples of innovations that led to the opening of new destinations. Institutional and informational innovations proliferated into critical modernization. A deeper comprehension of dissemination patterns can be useful toward future tourism innovation policies.